Declining diversity and abundance of High Arctic fly assemblages over two decades of rapid climate warming. Issue 2 (13th June 2017) - Loboda, Sarah; Savage, Jade; Buddle, Christopher M.; Schmidt, Niels M.; Høye, Toke T.
Abstract : Insects are particularly vulnerable to rapid environmental changes, which are disproportionally affecting high latitudes. Increased temperature could influence insect species differentially and reshape assemblages over time. We quantified temporal assemblage turnover of Arctic Diptera (flies) in the Muscidae, one of the most diverse and abundant families of Arctic insects, using time series data from Zackenberg, north‐east Greenland. We measured temporal patterns of abundance, diversity, and composition of muscid assemblages in wet fen, mesic and arid heath habitats from yearly collections spanning 1996–2014 and tested their relationship to climate. A total of 18 385 individuals representing 16 species of muscid flies were identified. A significant decrease of 80% of total muscid abundance was observed during the study period. Species richness declined in each habitat type but this trend was not significant across habitats. The number of common and abundant species also decreased significantly over time across habitats revealing a temporal modification of species evenness. Significant temporal changes in composition observed in the wet fen and across habitats were mainly driven by a change in relative abundance of certain species rather than by species replacement. Shift in composition in each habitat and decline in muscid abundance across habitats were associated with summer temperature, which has significantly increased over the study period. However, relationships between temperature and muscid abundance at the species level were noticeable for a few species only. Significant directional change in composition was documented in the wet fen but no biotic homogenization across habitats was observed. As one of the few studies of species‐level changes in abundance, diversity and composition of an insect taxon in the Arctic over the past two decades, our study shows that habitat types may modulate insect species responses to recent climate change and that contrasting species responses can alter species assemblages within a few decades.